2018
DOI: 10.3847/1538-4357/aaac2b
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Short Gamma-ray Burst Pulses from a BATSE TTE GRB Pulse Catalog

Abstract: We analyze pulse properties of Short gamma-ray bursts (GRBs) from a new catalog containing 434 pulses from 387 BATSE Time-Tagged Event (TTE) GRBs. Short GRB pulses exhibit correlated properties of duration, fluence, hardness, and amplitude, and they evolve hard-to-soft while undergoing similar triple-peaked light curves similar to those found in Long/Intermediate bursts. We classify pulse light curves using their temporal complexities, demonstrating that Short GRB pulses exhibit a range of complexities from sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 61 publications
3
52
0
Order By: Relevance
“…One SP (#07427) and one DP (#00575) in our sample are two EE bursts from Hakkila et al (2018a) and Bostancı et al (2013). However, we cannot fit the EE episodes with the pulse model because of their low signal-to-noise as in Hakkila et al (2018a). In practice, the EE components are more readily perceived in Swift/BAT mask-tagged data for sGRBs, we have examined in details their temporal and spectral properties and possible connections with main peak episodes (Li et al (2020), in preparation).…”
Section: Conclusion and Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…One SP (#07427) and one DP (#00575) in our sample are two EE bursts from Hakkila et al (2018a) and Bostancı et al (2013). However, we cannot fit the EE episodes with the pulse model because of their low signal-to-noise as in Hakkila et al (2018a). In practice, the EE components are more readily perceived in Swift/BAT mask-tagged data for sGRBs, we have examined in details their temporal and spectral properties and possible connections with main peak episodes (Li et al (2020), in preparation).…”
Section: Conclusion and Discussionmentioning
confidence: 82%
“…For brighter sGRBs, the EE component is sometimes detectable above the background (Norris & Bonnell 2006). One SP (#07427) and one DP (#00575) in our sample are two EE bursts from Hakkila et al (2018a) and Bostancı et al (2013). However, we cannot fit the EE episodes with the pulse model because of their low signal-to-noise as in Hakkila et al (2018a).…”
Section: Conclusion and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These analyses have identified "hard-to-soft" and "intensity tracking" behaviors (e.g., Wheaton et al (1973); Golenetskii et al (1983); Norris et al (1986); Paciesas et al (1992)), but this oversimplified bimodal classification scheme has been shown to represent a continuous range of behaviors (e.g., Kargatis et al (1994); Bhat et al (1994); Ford et al (1995); Borgonovo, & Ryde (2001)). Treating each GRB pulse as a structured episode rather than one in which pulses are statistically-significant intensity peaks, several studies (Liang & Kargatis 1996;Hakkila et al 2015Hakkila et al , 2018a have demonstrated that most pulses undergo and stretched at the time of reflection to show how well they match one another (the solid line represents the folded and stretched residuals preceding the time of reflection, while the dashed line represents the residuals following that time). The process used to identify time-reversality, as well as the fitted characteristics of this pulse, is described in Hakkila et al (2018b).…”
Section: Characteristics Of Grb Pulsesmentioning
confidence: 99%
“…Figures 3 and 6 are oversimplifications meant to represent generic situations. There is a spread of these alignments (e.g., see Figure 19 in Hakkila et al (2018a)), and a prime example of a pulse in which these are offset is BATSE 143p1 (see Figure 1 in Hakkila et al (2018b)). In addition to this offset, pulse residuals are not always folded at the peak of the residual function; many pulses have time-reversed residual structures for which the time of reflection does not occur other at the maximum of the residual function (see Figures 14-16 in Hakkila et al (2018b)).…”
Section: Alignment Of the Residuals With The Monotonic Pulse Componentmentioning
confidence: 99%